Relationship and innovation orientation in a business-to-business context - G. Human; P. Naudé (South African Journal of Business Management, 2010)
Market orientation and innovation orientation, including their relationship with firm performance, are well-debated in prevailing marketing literature. Interestingly, relationship orientation, as an extension of market orientation, is yet to be subjected to similar investigation. While relationship orientation suggests that firms should invest in building relationships with clients and suppliers to generate improved financial performance, innovation orientation proposes that customers will prefer superior and innovative products/services and it supports a learning philosophy. Torn between two shores, the result is often that practitioners are confused as to what the desired orientation for the firm should be. This paper considers the relationship of both orientations with firm performance in business-to-business (B2B) markets simultaneously, and in particular examines the mediating effect of innovation on the relationship orientation-firm performance relationship. By employing published scales for innovation and relationship orientation, cross-sectional data were collected from 181 business-to-business managers in South African firms. Confirmatory factor analysis was used to test for scale reliability and validity, while the hypothesized relationships between constructs were considered through structural equation modelling and partial least squares analysis. The paper provides valuable insights for measuring these constructs in an emerging market context and suggests a balanced approach to adopting these strategic orientations in B2B markets. The results suggest that practitioners and researchers should pay attention to both orientations simultaneously, because jointly they are associated with better firm performance.
Keywords: 650